Giant Cell-rich Osteosarcoma: unravelling an elusive, enigmatic entity - Imran, Ambreen A; Khaleel, Muhammad Eyyaz; Salaria, Sarosh Majeed; Hasan, Munazzah (International Journal of Pathology, 2018)
Abstract: Giant cell-rich osteosarcoma needs to be differentiated from malignant giant cell tumor as there aremarked differences in prognoses and treatment. There is considerable overlap in signs, symptoms andhistopathological features. We describe here a 16 year old girl who presented with pain and swelling below theknee joint and underwent an incisional biopsy. In the light of radiological and pathological features a diagnosis ofGiant cell-rich osteosarcoma was made